PELAKSANAAN LELANG EKSEKUSI OLEH DIREKTORAT JENDERAL BEA DAN CUKAI TERHADAP BARANG YANG DINYATAKAN TIDAK DIKUASAI (STUDI PADA KANTOR PELAYANAN KEKAYAANNEGARA DAN LELANG (KPKNL) DI KOTA MEDAN - PESTA ASPITA DIANA SIMANJUNTAK (PREMISE LAW JURNAL, 2013)
ABSTRACT The implementation of the Foreclosure Sale of the goods is stipulated in the Regulation of the Minister of Finance No. 93/PMK.06/2010 on the Operational Manual of Auction and the Regulation of the Director General of the State’s Property No PER-03/KN/2010 on the Operational Manual of the Implementation of Auction. Uncontrolled goods is the goods which has been informed its customs but is not removed from the Temporary Depot in the harbor area within 30 (thirty) days since it was kept, the goods which is not removed from the Temporary Depot outside the harbor area within 60 (sixty) days since it was kept, goods which is not removed from the Supplementary Bonded Depot whose license is suspended within 30 (thirty) days since the suspension, and goods which is sent via mail, rejected by the receiver, and not able to be resent because of the rejection or not arrived at the right address, and not settled by the sender within 30 (thirty) days since the information by the Post Office. The result of the research showed that the Regulation of the Minister of Finance No. 93/PMK.06/2010 on the Operational Manual of Auction has accommodated the implementation of auction, including the auction of uncontrolled goods. Keywords : Foreclosure Sale, Uncontrolled Goods, KPKNL